Horacio Quiroga ante la pantalla - Rocca, Pablo (Anales de Literatura Hispanoamericana, 2003)
This essay intends to analyse Horacio Quiroga’s connection with cinema. This relation was developed not only in the field of cinema criticism but also creating scripts, as well as the influence the new art had on some of his tales. From 1918 the connection between cinema and theatre or cinema as a business usually appears on his texts.